2021
DOI: 10.1155/2021/8620873
|View full text |Cite
|
Sign up to set email alerts
|

Backstepping Control Based on Constrained Command Filter for Hypersonic Flight Vehicles with AOA and Actuator Constraints

Abstract: An antisaturation backstepping control scheme based on constrained command filter for hypersonic flight vehicle (HFV) is proposed with the consideration of angle of attack (AOA) constraint and actuator constraints of amplitude and rate. Firstly, the HFV system model is divided into velocity subsystem and height subsystem. Secondly, to handle AOA constraint, a constrained command filter is constructed to limit the amplitude of the AOA command and retain its differentiability. And the constraint range is set in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…Existing nonholonomic constraint studies can be found in references [23][24][25][26], whereas input saturation studies can be found in references [27][28][29][30][31]. It is worth mentioning that the robust backstepping approach or the sliding mode approach is a powerful approach for controlling the nonholonomic system with input constraints [32][33][34]. However, there may be some problems such as introducing more complex structures, relying on more system information, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Existing nonholonomic constraint studies can be found in references [23][24][25][26], whereas input saturation studies can be found in references [27][28][29][30][31]. It is worth mentioning that the robust backstepping approach or the sliding mode approach is a powerful approach for controlling the nonholonomic system with input constraints [32][33][34]. However, there may be some problems such as introducing more complex structures, relying on more system information, etc.…”
Section: Introductionmentioning
confidence: 99%